Linguistic Validation of the LupusQoL for the Assessment of Quality of Life in Iranian Patients with Systemic Lupus Erythematosus - Naeimehossadat Hosseini (International Journal of Rheumatology, 2014)
Objectives. We evaluated the psychometric properties of the Persian LupusQoL for the evaluation of quality of life in Iranian systemic lupus erythematosus (SLE) patients. Methods. The LupusQoL was translated to Persian language. Patients with SLE (n=78) completed the LupusQoL and the Short-Form Health Survey (SF-36). Disease activity and cumulative disease damage were assessed with standard indices. The psychometric properties of the scale were evaluated. Results. The Cronbach’s alpha was 0.97 for the total LupusQoL (above 0.8 for subscales). There were strong corrected item-total (r>0.4), item-subscale (r≥0.5), and subscale-total correlations (r>0.6), as well as intersubscale correlations (r>0.5). Patients with active disease and patients with disease damage index of ≥1 had lower scores in domains of planning, emotional health, burden to others, and body image than patients with inactive disease and those with no disease damage, respectively (P<0.05). The LupusQoL and the SF-36 correlated well regarding comparable domains (r>0.4). Conclusion. The psychometric characteristics of the Persian version of LupusQoL questionnaire are acceptable in Iranian population. This instrument can be used to evaluate quality of life in Iranian SLE patients.